Temperature dependence of impedance spectrum of charge-transfer processes in lithium-ion batteries with nickel-manganese-cobalt cathode and graphite anode. (15th December 2021) - Inui, Yoshitaka; Hirayama, Satoshi; Tanaka, Tadashi
Highlights: The impedance spectra of charge-transfer processes in LIBs were measured by EIS. An ECM of LIBs was introduced and values of its circuit constants were identified. Temperature dependence of all of the identified circuit constants was made clear. A new method to estimate temperature dependence of impedance spectrum was proposed. Abstract: The temperature dependence of the impedance spectrum of charge-transfer processes in lithium-ion batteries with nickel-manganese-cobalt cathode and graphite anode within a range of 10 to 40 °C was investigated. The authors prepared eight test batteries by degrading two kinds of lithium-ion batteries having different manufacturer models through different degradation processes. Their impedance spectra were measured under various temperature and state of charge conditions. A corresponding equivalent circuit model was introduced and the values of its circuit constants were identified for all of the measured impedance spectrum data through fitting calculations. The authors then quantitatively evaluated the temperature dependence of all of the identified circuit constants. The Arrhenius type temperature dependence was confirmed for each charge-transfer resistance. Whereas, it was revealed that the temperature dependence of all other circuit constants is negligible. Using the obtained evaluation results, the authors proposed a novel method to estimate the impedance spectrum of charge-transfer processes under any battery temperature condition within a range of several degrees to several tens of degrees Celsius from spectrum data measured under a freely selected battery temperature condition within this range. The validity of the proposed method for its practical use was confirmed through comparison between estimated and measured results.